Comparison between sieve analysis & hydrometer with laser particle analyzer to determine particle size distribution - Rohaya, Rasmin (2011)
Determination of soil particle size distribution (PSD) by sieving, hydrometer as well as by laser particle analyzer suffers from inherent flaws, mainly due to the difficulty in defining the size of irregularly shaped particles. Therefore these methods yield only estimates of particle size distribution. The objective of this study was to determine a functional relationship exists between the PSDs obtained by the combined sieve-hydrometer method and those obtained by laser particle analyzer. Samples from 3 different places in Kuantan were analyzed. For the laser particle analyzer CILAS Particle analyzer were used employing the Mie theory. Values of 1.5 and 0.2 for the real part and the imaginary term of the reflective index, respectively, gave satisfactory results for the optical model calculations. Volume percentage of the clay-size fraction obtained by laser particle analyzer was generally lower than mass percentage of the clay fraction derived by the combined sieve & hydrometer method. The opposite trend was noted for the silt-size fraction. Coefficient of determination for the regression equations for the clay, silt, and sand fractions determined by the two methods were 0.702, 0.689, and 0.821, respectively. Good agreement between measured and calculated laser particle analyzer values for one size class was accompanied by poor agreement between measured and calculated values for the other. The laser particle analyzer method provides a continuous particle size distribution curve, which enables a detailed data analysis and a flexible application of different particle size distribution dependent classification system.